The Role of Green Marketing in Forming Mental Imagery for Customer: A Field Study of the Point of View of Specialists in Yemen Standardization Metrology & Quality Control Organization in the Municipality of Capital - Al-Mekhlafi, Abdulaziz Mohammed; Al-Arasi, Abeer Mohammed Ali (University of Science and Technology Journal for Management and Human Sciences, 2025)
The study aimed to identify the role of green marketing in its dimensions: (waste elimination or reduction, environmental orientation, green product, government pressure groups) in forming the consumer's mental image in its dimensions: (cognitive dimension, emotional dimension, procedural dimension (behavioral)) from the point of view of specialists in the Yemen Standardization Metrology & Quality Control Organization in the capital, and to achieve the objectives of the study and test its hypotheses, the analytical approach was used. The questionnaire was used as a tool to collect data from members of the study community. The study community consisted of (270) elements of specialists in the organization. The study used the comprehensive inventory method due to the small size of the study community. The data were entered, coded and analyzed using the (SPSS) program. The results of the study concluded that there is a positive role with statistical significance for green marketing in forming the consumer's mental image from the point of view of specialists in the organization, and it also concluded that there is a role with statistical significance for the two dimensions (waste elimination or reduction and government pressure groups) in forming the consumer's mental image from the point of view of specialists in the organization. Based on the results reached, the study recommended paying attention to practicing green marketing in industrial facilities, as it plays a role in raising the quality of the local product and consumer safety, thus creating a positive mental image in the consumer.
Keywords: green marketing; mental imagery for customer; Yemen Standardization Metrology & Quality Control Organization in the Municipality of Capital